Entre cuerpos olvidados y guerras vividas (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The present text consists of the author's unpublished dramaturgy. The plot unfolds between the jungle and the city of Bogotá, revealing the philosophical and political twists that weave their lives into a network of mysteries. The protagonists confront their own humanity and discover a devastating truth that threatens to crumble everything they tried to rebuild. The play explores the duality of internal and external struggle, questioning freedom, political manipulation, and the very essence of human existence. The drama culminates in an unavoidable tragedy that poses profound existential questions and challenges the perception of fate and redemption.
Keywords: political; philosophical; jungle; Bogotá; duality